Pengembangan skill wirausaha mahasiswa STIE Ganesha melalui Program Pembinaan Mahasiswa Wirausaha (P2MW) Kemdikbudristek RI Tahun 2022 - Aep Saefullah; Syarif Hidayatullah; Ekky Noviar; Ahmad Fadli; Tuti Herawati; Nurhayati Nurhayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
P2MW is a business development program for fifth-semester undergraduate students who own a business. Through development and coaching funds, it offers business assistance and coaching. Ten students were divided into three student business groups. Food and beverage businesses in the creative industry are divided into two categories: seafood and frozen food, and handicrafts. During field activities, students are accompanied and mentored by lecturers who serve as supervisors. The goal of this community service is to ensure that student business groups follow the Entrepreneurial Student Development Program (P2MW) guidelines and that reporting is completed on time. The activity took place at the STIE Ganesha campus for four months, from August to November. Online and offline mentoring, coaching, and coaching are methods of carrying out activities. Offline mentoring activities include discussions, advice, consultation, and visits (visits). Online activities include mentor account assessments, https://kesejahteraan.kemdikbud.go.id. The STIE Ganesha student business group completed a series of P2MW in 2022 in accordance with the Directorate of Student Learning, the Directorate General of Higher Education, and Research Technology RI implementation instructions and guidelines. P2MW activities benefit the advancement of the entrepreneurial ecosystem in universities as well as the smooth operation of student businesses.